Umur Simpan Telur Puyuh Yang Direndam Dalam Ekstrak Etanol Kulit Manggis (Garcia Mangostana L ) terhadap Kualitas Fisik Telur Puyuh: Shelf Life of Quail Eggs Soaked in Ethanol Extract of Mangosteen Peel (Garcia Mangostana L ) on Physical Quality of Quail Eggs - Habiburrochman, Moh; Mudawaroch, Roisu Eny; Iskandar, Faruq (Jurnal Riset Agribisnis dan Peternakan, 2022)
The aim of this study was to determine the storability of quail eggs at room temperature by treating the level of mangosteen peel extract (Garcia Mangostana L) on the physical quality of quail eggs. This study used 126 quail eggs soaked for 1 hour and stored for 3 weeks. The research design was a completely randomized design (CRD) with 4 treatments and 3 replications. Administration of mangosteen peel ethanol extract had no significant effect on the egg index with values of 77.98, 70.42, 70.42 and 80.46. The egg white index values had a significant effect of 0.50, 0.024, 0.018 and 0.014. The egg yolk index values had a significant effect of 0.41, 0.17, 0.11 and 0.11. The value of egg yolk color had no significant effect at 4.09, 4.04, 4.04 and 4.04. The pH value of egg white had a significant effect of 7.89, 8.56, 8.7 and 8.42. The pH value of the egg yolk had a significant effect (P<0.05) of 6.22, 6.74, 7.22 and 7.42. Most of the concentration of mangosteen rind ethanol extract had no significant effect except on the pH of the egg yolk. The storability of quail eggs mostly had a significant effect except for the egg index and the color of the yolk. There is no interaction between immersion level and storage capacity.